TAFII mutations disrupt dorsal activation in the Drosophila embryo. - Zhou, J.; Zwicker, J.; Szymanski, P.; Levine, M.; Tjian, R. (Proceedings of the National Academy of Sciences of the United States of America, 1998)
In this study, we present evidence that the Dorsal activator interacts with limiting amounts of the TFIID complex in the Drosophila embryo. In vitro transcription reactions and protein binding assays implicate the TAFII110 and TAFII60 subunits of the TFIID complex in contributing to Dorsal-mediated activation. Mutations in TAFII110 and TAFII60 result in altered patterns of snail and twist transcription in embryos derived from dl/+ females. These results suggest that TAFIIs contribute to the activation of transcription in vivo and support the hypothesis that subunits of TFIID may serve as targets of enhancer binding proteins.